Impact of epidermal growth factor receptor gene RS1468727 polymorphism on survival of the patients with oral squamous cell carcinoma - Bačulov Katarina; Đan Mihajla; Bajkin Branislav; Mijatov Ivana; Vučković Nada; Mijatov Saša; Đan Igor; Barjaktarović Iva; Stojčević-Maletić Jelena; Vučinić Nataša (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction/Objective. Genetic aberrations and environmental factors are known to play an important role in oral squamous cell carcinoma (OSCC). The aim of the study was to clarify the association of epidermal growth factor receptor (EGFR) gene polymorphism rs1468727 with overall survival (OS) in patients with OSCC. Methods. The study comprised a total of 61 patients diagnosed with OSCC. The follow-up period for each patient was three years from the date of surgery and during that period their genotypes for rs1468727 polymorphism of the EGFR gene were identified using real-time polymerase chain reaction. Binary logistic regression was used to investigate the influence of various variables on survival. Additionally, the χ2 test of independence and Man–Whitney U test were done to examine the interplay between two categorical variables and two independent samples. Results. Two variables demonstrated a statistically significant influence on OS: the TNM Classification of Malignant Tumors (TNM) stage and EGFR genotype. At the end of the follow-up period, 39 patients survived, with a noteworthy observation that more than half of the survivors had the EGFR rs1468727 CC genotype. The distribution of CC and CT genotypes was equal (χ2 = 0.397, df = 2, p = 0.820) among patients who deceased, indicating that no statistically significant correlations were found between OS and demographic or tumor-related characteristics. Conclusion. EGFR rs1468727 homozygote (genotype CC) and TNM stage showed statistically significant influence on OS in the follow-up period. This study highlights the potential significance of homozygote EGFR rs1468727 CC in assessing the prognosis and treatment outcomes of patients undergoing surgery for OSCC.